PENGARUH KUALITAS PELAYANAN, SUASANA TOKO, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI INDOMARET JALAN SULTAN ISKANDAR MUDA KEBAYORAN LAMA - Lucy Nancy Simatupang; Husnul Hotimah (Jurnal Manajemen, 2019)
This study aims to determine the effect of Service Quality, AtmosphereStore, and Location on Purchasing Decisions at Indomaret Jalan Sultan Iskandar Muda Kebayoran Lama. The population in this study all consumers who made purchases at Indomaret Jalan Sultan Iskandar Muda Kebayoran Lama and the sample in this study amounted to 71 consumer. The design of this study uses a causal method. The sampling technique uses accidental sampling. The method of collecting data uses primary data and secondary data.The data analysis method used in this study is multiple linear regression analysis with the help of SPSS 22 Software.The results showed that partially (t test) Service Quality (X1) and AtmosphereStore (X2) had a significant effect on Purchasing Decisions,while Location (X3) had no significant effect on Purchasing Decisions.Simultaneously (F test) shows that there is a significant influence between Service Quality variables (X1), AtmosphereStore (X2) Location (X3) on Purchase Decisions (Y).And the contribution of all adjusted R2 independent variables is 49,6% towards Purchasing Decisions (Y), while the remaining 50,4% is explained by other factors or variables unknown and not included in this study